Intestinal Epithelial Cells-Derived Hypoxia-Inducible Factor-1α Is Essential for the Homeostasis of Intestinal Intraepithelial Lymphocytes - Sun, Lihua; Li, Teming; Tang, Hanlin; Yu, Kun; Ma, Yuanhang; Yu, Min; Qiu, Yuan; Xu, Pengyuan; Xiao, Weidong; Yang, Hua (Frontiers in Immunology, 2019)
Hif-1α is a master regulator which involved in the transcriptional regulation of anti-inflammatory or cellular response to hypoxia. Previous work shows that the absence of Hif-1α results in the destruction of intestinal epithelial cell (IEC) and abnormalities of intestinal barrier function. However, we know very little about other functions of Hif-1α on intestinal intraepithelial lymphocyte (IEL). Here, we generated a transgenic mouse (Hif1-αΔIEC mice), which knock out Hif1-α specifically in IECs, to study the effect of Hif1-α on IEL. IELs were isolated from the small intestine and colon of mice respectively and examined by flow cytometry and quantitative real-time PCR. All cytokines expression was detected by quantitative real-time PCR. The experimental colitis was induced by administration of 2.5% DSS. We found the numbers of IELs is increased in Hif1-αΔIEC mice. It is showed that knockout of Hif1-α in IECs led to significant changes in IEL phenotype, including a marked decline in the CD8αα+ and TCRγδ+ populations. The reduction of CD8αα+ IELs is accompanied by increased apoptosis, decreased proliferation and weakened migration in Hif1-αΔIEC mice. Moreover, absence of intestinal epithelial Hif1-α increases susceptibility to dextran sulfate sodium-induced colitis and changes microbial assemblage. In summary, our results first time demonstrate that IEC-derived Hif1-α is essential for maintaining IELs homeostasis and intestinal microbiota.